Improving Students Writing by Using Inside Outside Circle at IKIP PGRI Pontianak - Sulaiman, Sulaiman (Lembaga Penelitian Unswagati Cirebon Indonesia, 2018)
This research aims to describe (1) whether and to what extent the implementation of Inside Outside Circle technique improves studentsâ writing; (2) the difficulties which occur in implementing of Inside Outside Circle technique in improving studentsâ writing. This action research study is carried out on the third semester at private university in Pontianak.The research is carried out in 2 cycles. Every cycle consists of four steps: planning, implementing, observing, and reflecting. The qualitative data are collected by using techniques of observation and documentation, while quantitative data are collected by using test (pre-test and post-test). The qualitative data are analyzed through descriptive analysis which consists of assembling the data, coding the data, comparing the data, building interpretation, and reporting the outcomes. The quantitative data are analyzed through descriptive statistics. The research findings show that Inside Outside Circle technique can improve studentsâ writing and its difficulties found in the implementation.Key words: inside outside circle, writing, classroom action research